#TITLE_ALTERNATIVE# - (NIM 122 03 042) , Djabaruddin
Abstract Boberg-Lantz is one of methods that we use to predict production rate from Huff & Puff injection wells. This method describes stimulation process with cylinder analytic models using step functions for average injected temperature between fronts and back, we developed this method and now became semi-analytical models. We knew that Boberg-Lantz method failed to represent how productions increase until the maximum production rate. Start from this problem, the research is conducted to make better profile when productions increase until the highest production rate and time to reach it. Peak production time is a period for reservoir to reach the maximum production rate. Boberg-Lantz method does not analyze peak production time. This research is trying to modificate Boberg-Lantz method, which analyze sensitivity injection time and steam mass depends on peak production. This research has succeed to generate a new equation that more representative for maximum production rate in field case.